Phosphorus deposition accelerates wood decomposition and temperature sensitivity in a subtropical forest - Chunsheng Wu (Elsevier, 2021)
Phosphorus (P) deposition plays a vital role in determining forest productivity and influencing microbial decomposer communities and activities. Wood plays a key role in forest carbon (C) dynamics because it contains a sizeable proportion of total forest C. However, the effects of increasing P deposition on wood respiration (Rw) in subtropical evergreen forests are still unclear. In this study, we conducted a four-year field factorial fertilization experiment in a subtropical Chinese evergreen forest to investigate the influences of simulated changes in P deposition at three levels (e.g., 0 (control), 30 (P1), and 60 (P2) kg P/ha/yr) on the Rw of Lithocarpus glaber (Thunb.) Nakai (LI). We found that Rw showed significantly higher sensitivity (Q10) to wood temperature than to air temperature. The Rw rate was significantly and positively correlated with the wood microbial decomposer community (including fungi and bacteria), wood temperature and available P. Compared to the control treatment, the P1 and P2 treatments increased the mean annual Rw by approximately 1.82 and 0.98 times, respectively. P deposition also accelerated the Q10 of Rw. Meanwhile, on average, wood emitted 20.29 kg CO2/ha/yr per 1 kg P/ha/yr added, which declined when P deposition increased above a P saturation threshold of 30 kg P/ha/yr. Our results provide insights into the influences of P deposition on carbon dioxide emissions from wood and also on decomposition rates in subtropical evergreen forests under the rising temperatures expected in the coming decades.